The Contribution of Sociocultural Factors in Shaping Self-Reported Sickness Behavior - Shattuck, Eric C.; Perrotte, Jessica K.; Daniels, Colton L.; Xu, Xiaohe; Sunil, Thankam S. (Frontiers in Behavioral Neuroscience, 2020)
Sickness behavior is an evolutionarily conserved phenomenon found across a diverse range of animals and involves a change in motivational priorities to theoretically maximize energetic investment in immune function and recovery. Typical components of sickness behavior include reduced sociability and activity, changes in diet, and depressed affect. Importantly, however, sickness behavior appears to be subject to other demands of life history in animal models, including reproduction and offspring survival. Thus, "feeling sick" is often context dependent with possible effects on morbidity and mortality. While humans may not always face the same life history tradeoffs, sociocultural norms and values may similarly shape sickness behavior by establishing internalized parameters for "socially appropriate sickness." We explore the role of these factors in shaping sickness behavior by surveying a national US sample (n = 1,259). Self-reported and recalled sickness behavior was measured using the SicknessQ instrument, which has previously been validated against experimentally induced sickness behavior. After post-stratification weighting and correction for Type I error, generalized linear models show that sickness behavior is significantly affected by various factors across sex and racial/ethnic groupings. Income below the national mean (b = 1.85, adj. p = 0.025), stoic endurance of pain and discomfort (b = 1.61, adj. p < 0.001), and depressive symptomology (b = 0.53, adj. p < 0.001) were each associated with greater sickness behavior scores. Familism (b = 1.59, adj. p = 0.008) was positively associated with sickness behavior in men, but not women. Endurance of pain and discomfort was associated with greater sickness behavior in Whites only (b = 1.94, adj. p = 0.002), while familism approached significance in African Americans only (b = 1.86, adj. p = 0.057). These findings may reflect different social contexts of sickness across demographic groups, which may in turn have important implications for pathogen transmission and recovery times, potentially contributing to health disparities.Tables: 4